Impact of food hygiene and safety training on knowledge, attitude, and practices of food hygiene and safety practices among food handlers in boarding schools of Embu County, Kenya - Kaugi, Rosaline W.; Kariuki, John G.; Odongo, Alfred O.; Koech, Maureen J.; Njoroge, Harrison C. (International Journal Of Community Medicine And Public Health, 2023)
Background: The reduction of foodborne illnesses depends on the adoption and evaluation of effective food handling procedures in the food service industry. The purpose of the study was to evaluate the impact of food hygiene and safety training on the knowledge, attitudes, and practices of food handlers in boarding schools in Embu County, Kenya. Methods: A longitudinal nonequivalent quasi-experimental survey design was utilized. A sample size of 198 study respondents was generated, Magnani formula was used. Multistage sampling was applied to select the study participants. STATA version 17 was employed for data analysis. Results: The knowledge score changed from 71% at baseline to 90% at the end line compared to the control arm which did not significantly change. Attitude score changed from 71% at baseline to 89% at endline compared to the control arm which did not significantly change (64% to 63%). This corresponds to a DID change of 19 percent increase in the attitudes scores (p<0.001). Lastly, practices score changed from 63% at baseline to 93% at endline. This corresponded to a 34 percentage point increase in the practice scores (p<0.001). Conclusions: Overall, Knowledge, attitude and practices were low at baseline than at the endline survey. Statistically, the study revealed that knowledge, attitude, and practices were associated with adherence to food safety and hygiene standards. The Government through the Ministries of health and education should consider training of food handlers on food safety and hygiene for improved knowledge, attitude, and practices.